Beta event-related desynchronization as an index of individual differences in processing human facial expression: further investigations of autistic traits in typically developing adults - Cooper, Nicholas R.; Simpson, Andrew; Till, Amy; Simmons, Kelly; Puzzo, Ignazio (Frontiers in Human Neuroscience, 2013)
The human mirror neuron system (hMNS) has been associated with various forms of social cognition and affective processing including vicarious experience. It has also been proposed that a faulty hMNS may underlie some of the deficits seen in the autism spectrum disorders. In the present study we set out to investigate whether emotional facial expressions could modulate a putative EEG index of hMNS activation (mu suppression) and if so, would this differ according to the individual level of autistic traits (high versus low AQ score). Participants were presented with 3 second films of actors opening and closing their hands (classic hMNS mu-suppression protocol) while simultaneously wearing happy, angry or neutral expressions. Mu-suppression was measured in the alpha and low beta bands. The low AQ group displayed greater low beta ERD to both angry and neutral expressions. The high AQ group displayed greater low beta ERD to angry than to happy expressions. There was also significantly more low beta ERD to happy faces for the low than for the high AQ group. In conclusion, an interesting interaction between AQ group and emotional expression revealed that hMNS activation can be modulated by emotional facial expressions and that this is differentiated according to individual differences in the level of autistic traits. The EEG index of hMNS activation (mu suppression) seems to be a sensitive measure of the variability in facial processing in typically developing individuals with high and low self reported traits of autism.